THE INFLUENCE OF ORGANIZATIONAL JUSTICE, PERCEIVED ORGANIZATIONAL SUPPORT, INNOVATIVE WORK BEHAVIOR, EMOTIONAL INTELLIGENCE, AND ORGANIZATIONAL TRUST ON EMPLOYEE PERFORMANCE AT PT ALCON BATAM. - Marisa Nainggolan; Habibuddin Nasution; Hanafi Siregar; Annisa Rara Salvira (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
Employee performance is a critical determinant of organizational effectiveness in large, labor‑intensive manufacturing companies. This study examines the influence of organizational justice, perceived organizational support, innovative work behavior, emotional intelligence, and organizational trust on employee performance at PT Alcon Batam, Indonesia. Using a quantitative, causal‑associative design, data were collected from 400 employees selected through proportional stratified random sampling across major departments. The constructs were measured with a structured questionnaire on a five‑point Likert scale, and the data were analyzed using multiple linear regression after validity, reliability, and classical assumption tests were satisfied. The results show that all five variables have positive and statistically significant effects on employee performance, both partially and simultaneously, with emotional intelligence emerging as the strongest predictor. The regression model explains 60.8% of the variance in employee performance (R² = 0.608; F = 79.49; p < 0.001), indicating that fairness, perceived support, innovative behavior, emotional capabilities, and organizational trust jointly form a critical socio‑psychological foundation for enhancing performance in a large manufacturing context. These findings provide theoretically grounded and context‑specific implications for the design of integrated human resource management strategies in emerging economy settings.